The main pathogens of healthcare-associated infections in patients of neurosurgery intensive care unit and antimicrobial activity of the most used antibacterial drugs (Russian Medical and Social Journal, 2019)
Importance. Healthcare-associated infectionsare an important issue in the neurosurgery. The changes in the epidemiological structure of etiological agents, the increase of antimicrobial drug resistance may lead to the ineffectiveness of previously used patterns for the prevention and treatment of healthcare-associated infections.Objective.The aim of the research was to study the microbiological structure of leading etiological agents that cause healthcare-associated infectionsin patients of neurosurgery intensive care unitand to evaluate the effectiveness of the most used antibacterial drugs.Patients and Methods.A retrospective statistical analysis of the results of microbiological monitoring of pathogens of healthcare-associated infectionsin patients of neurosurgery intensive care unitin 2013-2017 was carried out.Results. The share of gram-negative microorganisms among all isolated microorganisms in the period 2013-2017 increased from 42.47% in 2013 to 54.10% and 50.68% in 2016 and 2017.K. pneumoniae, A. baumannii, P. aeruginosa were most often isolated among gram-negative pathogens, and S. aureus, E. faecalis, and S. Epidermidis- amonggram-positive pathogens; the total rate of these six microorganisms progressively increased from 58.91 % in 2013 to 80.51% in 2017. The rateof A. baumanniiincreased from 8.22% in 2013 to 15.58% in 2017 and the rate of K. pneumoniae- from 5.48% in 2013 to 14.29% in 2017, stable significant detectability of P. aeruginosatended to increase (from 9, 59% in 2013 to 11.69% in 2017). Enterococcus spp. was identified at a significantly high level, mainly E. faecalis and E. faeciumwere represented. E. faecalis dominated (10.96% in 2013, 12.35% in 2014, 10.24% in 2015, 8.70% in 2016, 6.49% in 2017) among the isolated Enterococcus spp. A dynamic decrease in the antimicrobial activity of most used antibacterial drugs was revealed. The greatest dynamic decrease in antimicrobial activity was observed in the aminoglycoside antibiotics - gentamicin and amikacin; amoxicillin / clavulanic acid and levofloxacin. The sensitivity to vancomycin and linezolidremained at levels close to 100%.Conclusions.Today recommendations for perioperative antibiotic prophylaxis with cefazolin remain relevant. When conducting empirical antibacterial therapy, it is justified to use a combination of vancomycin with the IIId generation cephalosporins until the results of a microbiological study are obtained. An increase in the rate of resistant microorganisms complicates antibacterial therapy, requires the usage of several antibacterial drugs and increase the importance of preventive actions.
Keywords: Healthcare-associated infections; Hospital acquiredinfections; Nosocomial infections; Intensive care infections; Cross-infections; Neurosurgery; Microbiological analysis; Microbial sensitivitytests; Anti-bacterial drugs; Anti-bacterial drug resistance; Anti-microbial activity